The Tunisian Intellectual in Contemporary Arab thought ; Muhammad al-Khidr Husayn is an Example - Said Karoui (Social Empowerment Journal, 2022)
The search for the truth calls for a deep dive into history, and a careful study of its folds. In order to know the roles of the predecessors among the Arab intellectuals in general and the Tunisians in particular, it became necessary to reveal the mission they undertook, and to show its impact on contemporary Arab thought and its impact, whether it was superficial or deep.In this regard, Sheikh Muhammad Al-Khidr Hussein (1876-1958) contributed to enriching contemporary Arab thought through his scientific and intellectual productions, and his political and social activities, as a Tunisian Arab intellectual.